2015
DOI: 10.1200/jco.2014.57.3568
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Attendance by Patients With Cancer in Their Last Month of Life: A Systematic Review and Meta-Analysis

Abstract: We identified demographic (men; black race), clinical (lung cancer), and environmental (low SES; no palliative care) factors associated with an increased risk of ED attendance by patients with cancer in their last month of life. Our findings may be used to develop screening interventions and assist policy-makers to direct resources. Future studies should also investigate previously neglected areas of research, including psychosocial factors, and patients' and caregivers' emergency care preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 68 publications
8
106
3
Order By: Relevance
“…For example, lack of access for rural residents to community-based services after clinical hours likely increases reliance on hospital care. That finding is supported by numerous studies [13][14][15] . Further work is needed to better understand the landscape of end-of-life care in Canada:…”
Section: Discussionsupporting
confidence: 77%
“…For example, lack of access for rural residents to community-based services after clinical hours likely increases reliance on hospital care. That finding is supported by numerous studies [13][14][15] . Further work is needed to better understand the landscape of end-of-life care in Canada:…”
Section: Discussionsupporting
confidence: 77%
“…39 Palliative care consultations for patients with advanced cancer have also been shown to reduce the quantity and intensity of life-prolonging care received toward the EOL. [40][41][42][43][44] Conversely, the lack of palliative care team consultation has been shown to be a predisposing factor for futile life-sustaining treatments at EOL. 45 An observational study suggested that inpatient palliative care led to fewer or no transitions in care settings at EOL.…”
Section: Eol Care In Oncologymentioning
confidence: 99%
“…These services have been associated with a reduced need for EOL emergency department visits, reduced length and frequency of hospitalization, and fewer intensive care unit (ICU) admissions and in-hospital deaths. [40][41][42][43][44] Palliative care has been shown to reduce symptom burden, improve QOL, and increase the odds of dying at home. Similarly, a 2013 Cochrane Database systematic review that analyzed home palliative care in patients with advanced illness demonstrated a reliable reduction of symptom burden and an increased likelihood of dying at home without a negative impact on caregiver grief.…”
Section: Eol Care In Oncologymentioning
confidence: 99%
“…Among factors influencing hospital deaths are underlying cause of death, for example hematological cancer, and the availability of acute hospitals and inpatient beds, whereas factors influencing home deaths include living with relatives, having a partner and socioeconomic status [3]. Other factors that seem to influence hospital deaths are emergency department attendance in the last month of life for people with low socioeconomic status, being male and dying of lung cancer [9]. Metropolitan populations have been shown to be less likely to die at home in some countries [10], and impact of socioeconomic deprivation varies by geographical region rather than urban or rural residence [11].…”
mentioning
confidence: 99%